THE SHORT STORY LE PAPA DE SIMON: GUY DE MAUPASSANT’S SOCIAL CRITICISM OF 19TH CENTURYFRENCH SOCIETY: CERPEN LE PAPA DE SIMON: KRITIK SOSIAL GUY DE MAUPASSANT PADA MASYARAKAT PERANCIS ABAD XIX - Tania Intan; Sri Rijati (Jurnal Kata, 2021)
Literary work is not only a reflection of the socio-cultural conditions of a particular time but also a display of its people’s development of thinking. This study aims to describe the social situation of French society in the nineteenth century portrayed in the short story ‘Le Papa de Simon’ by Guy de Maupassant and explain the social criticism conveyed by the author. The method used in this study is descriptive qualitative. Data in the form of words, phrases, and sentences were collected by library study techniques. Data in French were translated by the researcher and the results validated by native speaker. Data analysis was performed by grouping, interpreting, and studying the sociology of literary approach. The results of the study prove that (1) all narrative elements of the short story supported the depiction of social conditions (2) regarding the institution of marriage, family values and religion in nineteenth-century French society. (3) In addition to reflecting human character, Maupassant also proposes social criticism primarily related to the impact of low education, poverty,  social inequality and the discrimination of women. From this study, it was found that the author conveyed his criticism of human cruelty in society, which often resulted from obeying to rules and norms.